Response of buried box-shaped road tunnel against internal BLEVE and its damage mitigation - Cheng, Ruishan; Chen, Wensu; Hao, Hong; Li, Jingde (2023)
Box-shaped road tunnels have been widely used in urban areas and might face the threats of accidental Boiling Liquid Expansion Vapor Explosions (BLEVEs) due to ever-increasing liquified petroleum transportation. However, very limited study has investigated the response of popularly used buried box-shaped road tunnels (i.e., box-shaped tunnels buried in soil mass) subjected to internal BLEVEs. In this study, the dynamic response of a typical two-cell box-shaped road tunnel buried in soil subjected to internal BLEVEs induced by the burst of a 20 m3 liquified petroleum gas (LPG) tank is numerically investigated by using LS-DYNA. The results show that the tunnel experiences severe damage under BLEVEs with liquid-filling ratios equal to or more than 65% while it suffers only minor damage with the load carrying capacity not compromised under BLEVE with 50% filled-liquid. The effects of BLEVE occurring locations on the tunnel response are then investigated. It is found that the tunnel subjected to the BLEVE occurring on the lane near middle wall experiences more significant response in general than that away from the middle wall. In addition, to mitigate the tunnel damage under BLEVEs, strengthening soil mass around the tunnel using soil–cement mixture is considered and its performance is examined. An empirical formula is also proposed for the design of using soil–cement mixture to enhance the buried box-shaped tunnel against internal BLEVEs.